2020
DOI: 10.1042/cs20200486
|View full text |Cite
|
Sign up to set email alerts
|

ACE2, angiotensin 1-7 and skeletal muscle: review in the era of COVID-19

Abstract: Angiotensin converting enzyme-2 (ACE2) is a multifunctional transmembrane protein recently recognised as the entry receptor of the virus causing COVID-19. In the renin–angiotensin system (RAS), ACE2 cleaves angiotensin II (Ang II) into angiotensin 1-7 (Ang 1-7), which is considered to exert cellular responses to counteract the activation of the RAS primarily through a receptor, Mas, in multiple organs including skeletal muscle. Previous studies have provided abundant evidence suggesting that Ang 1-7 modulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 166 publications
1
39
0
6
Order By: Relevance
“…RAS components are expressed in satellite cells and contribute to muscle regeneration and age-associated muscle changes [ 38 ]. Importantly, abundant evidence suggested that the protective axis of tRAS protects from pathological muscle remodeling and muscle insulin resistance [ 39 ]. The workgroup of Delafontaine et al sowed that AngII was working through NADPH and mitochondria-derived ROS generation [ 40 ].…”
Section: Summary Of Study Findings: Tras and Its Tole In Human Tismentioning
confidence: 99%
“…RAS components are expressed in satellite cells and contribute to muscle regeneration and age-associated muscle changes [ 38 ]. Importantly, abundant evidence suggested that the protective axis of tRAS protects from pathological muscle remodeling and muscle insulin resistance [ 39 ]. The workgroup of Delafontaine et al sowed that AngII was working through NADPH and mitochondria-derived ROS generation [ 40 ].…”
Section: Summary Of Study Findings: Tras and Its Tole In Human Tismentioning
confidence: 99%
“…The deleterious crosstalk between RAGE and RAS might be active also in the muscles of severe COVID-19 patients who develop cachexia [108], a complex metabolic syndrome characterized by the loss of muscle mass and body weight, since both RAGE and RAS signals play crucial roles in inducing muscle protein breakdown [109]. Skeletal muscle tissue expresses a considerable amount of ACE2 [110], making muscles potential targets of SARS-CoV-2. Deletion of ACE2 in mice translated into early manifestations of muscle weakness with signatures of muscle senescence [111], suggesting that the SARS-CoV-2dependent downregulation of ACE2 might predispose COVID-19 patients to cachexia.…”
Section: Rage and The Renin-angiotensin System Overlapping Pathways And Biased Signaling With Potential Relevance In Covid-19mentioning
confidence: 99%
“…Indeed, mechanical ventilation, the main supportive therapy for ARDS patients, induces ventilator-induced diaphragmatic dysfunction (VIDD) [44] , which is characterized by a contractile dysfunction and a rapid muscular atrophy [45] . Muscular disorders may result from a RAS imbalance [46] . It has been shown that Ang-II induces diaphragm muscle wasting and respiratory muscle dysfunction [47] , whereas Ang-(1–7) exerts a protective action in a rat model of VIDD [48] and could improve muscular functions in patients infected by SARS-CoV-2 [46] .…”
Section: Potential Beneficial Effects Of Restoring Ras Balance Througmentioning
confidence: 99%
“…Muscular disorders may result from a RAS imbalance [46] . It has been shown that Ang-II induces diaphragm muscle wasting and respiratory muscle dysfunction [47] , whereas Ang-(1–7) exerts a protective action in a rat model of VIDD [48] and could improve muscular functions in patients infected by SARS-CoV-2 [46] .…”
Section: Potential Beneficial Effects Of Restoring Ras Balance Througmentioning
confidence: 99%